Analysis Of Use Behavior In The Perspective Of The UTAUT In The Procurement Of Government Goods And Services At The Regional Secretariat Of Magelang City - Reva Ngulya Savi’ah; Joko Tri Nugraha; Yuni Kurniasih; Matheus Gratiano Mali (Jurnal Info Sains : Informatika dan Sains, 2024)
E-procurement transformation aims to increase effectiveness and efficiency in order to minimize budget expenditure while obtaining the goods/services needed at reasonable and cheap prices with the best quality. In 2023, the Magelang City Government received an award as the best goods/services procurement manager in Central Java, however, there are obstacles such as employees still having difficulty operating E-procurement, resulting in procurement ineffectiveness and inefficiency. These constraints support the confirmation of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model. The aim of the research is to identify the influence of variables in the UTAUT 2 model on the implementation of E-procurement by government goods/services procurement employees in Magelang City. This research uses a confirmatory quantitative method with a cross-sectional design processed using PLS-SEM. The research results show that there are 4 accepted hypotheses, including Social Influence and Habit have a significant effect on Behavioral Intention, and Facilitating Conditions and Behavioral Intention have a significant effect on Use Behavior. Meanwhile, the 6 hypotheses that were rejected, namely Performance Expectancy, Effort Expectancy, Facilitating Condition, Hedonic, and Price Value, had no significant effect on Behavioral Intention, and Habit had no significant effect on Use Behavior. Suggestions that can be given to increase the adoption of E-Procurement acceptance are by conducting regular and periodic outreach and training.